Prevalence of Atopic Dermatitis among Korean Adults Visiting Health Service Center of the Catholic Medical Center in Seoul Metropolitan Area, Korea - Kim, Min Joo (The Korean Academy of Medical Sciences, 2010)
The point prevalence of atopic dermatitis (AD) among Korean adults visiting the Health Service Center for health check-ups was assessed. AD was diagnosed based on the questionnaires filled by patients and through physical examination by dermatologists. A total of 3,563 persons completed the questionnaires, and 2,032 persons were examined by the dermatologists. According to the questionnaires, the prevalence of AD was 7.1%, and from the dermatologists' examination, it was 2.6% overall, which decreased with age significantly. The prevalence in men was higher than that of women. Grading the severity of AD according to their eczema area and severity index scores, 70.6% were classified as being mild, 25.5% moderate, and 3.9% severe. Interestingly, concomitance of psoriasis and AD was found in 0.5% of those examined by the dermatologists. Our results suggest that AD is one of the most common skin diseases not only in children but also in adults in Korea.